Dlaczego w poezji późnego średniowiecza funkcjonują tylko dwa wersety Modlitwy Pańskiej? - Masłej, Dorota (Slavia Occidentalis, 2015)
The goal of this article is to provide an answer why late-Medieval poetry offers only two verses of the Lord’s Prayer. An analysis of the existing literature leads to a conclusion that only two requests exist, transformed in different ways: “forgive us our trespasses” and “but deliver us from evil”. The author of the article views this phenomenon in a broader context of the late medieval culture and explains the phenomenon by referring to the existing knowledge of the process of Christianisation in medieval Poland. An analysis of late medieval poetry with respect to the position of the Lord’s Prayer results in methodological conclusions (it is difficult to evaluate the nature of a specific fragment in a text due to the non-existent canonical version of the prayer) and conclusions about the language and the culture (the then religiosity). The absorption of the Lord’s Prayer is evident only in relation with fear and the broadly-defined superstitions as resulting from the intertwining Catholic and pagan beliefs. Their influence is reflected in late medieval literature where specific prayerrelated phrases were taken over. Quite possibly, this procedure was involuntary and unintentional. While the phrases lost their strictly prayer character, they managed to retain their magical function of such importance to praying.